2020
DOI: 10.1007/s40558-019-00163-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploration and implication of factors affecting e-tourism adoption in developing countries: a case of Nepal

Abstract: E-tourism plays a pivotal role in delivering services to tourists by enhancing travel experiences. While small tourism service providers in the developed economies can efficiently take advantage of e-tourism by partnering with global online platforms such as TripAdvisor or Booking.com, small tourism service providers in developing countries often struggle to reach global markets due to factors that are unique to the country they operate in. The aim of this study, therefore, is to identify the key barriers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…The government's role in e-collaboration activities is to support, encourage, assist, and foster collaboration. The government is also expected to be the driving force, providing funding (e.g., grants or low-interest loans) and business referrals, including policy [77]. Governance and monitoring can be prepared so that e-collaboration activities can produce results following its objectives.…”
Section: -2-the E-collaboration Strategiesmentioning
confidence: 99%
“…The government's role in e-collaboration activities is to support, encourage, assist, and foster collaboration. The government is also expected to be the driving force, providing funding (e.g., grants or low-interest loans) and business referrals, including policy [77]. Governance and monitoring can be prepared so that e-collaboration activities can produce results following its objectives.…”
Section: -2-the E-collaboration Strategiesmentioning
confidence: 99%
“…Lack of Supplier Support refers to suppliers' low postsales services in customer refunds, customer travel issues, poor supplier responses, no dedicated service staff assigned to attend to Travel Agency issues, and attitude/behavioral responses of support staff in personal interactions (Field Study, 2018). Sila (2013), in his study of SMEs in developing countries, identified Supplier Trust; Bigne et al (2008), in their survey of travel agencies in Spain, identified B2B relationship intensity; and Lama et al (2020) in their tourism research in Nepal, identified Lack of Supplier Trust as an inter-organizational factor. According to Agency theory (Eisenhardt, 1989), the online travel suppliers (Principal) drive to align the behaviours or outcomes of the other parties-retail travel agencies (Agents) to their expectations.…”
Section: Influence Of Perceived Barriers On the Degree Of Digital Usementioning
confidence: 99%
“…In our study, we find that interorganizational factors are identified in the retail travel agency literature in the context of B2B relationships. A retail travel agency digital usage study in Spain identifies the inter-organizational factor of B2B relationship intensity (Bigne et al, 2008) and lack of supplier trust in SME tourism agents study in developing countries of Nepal (Lama et al, 2020). The study of B2B e-commerce adoption for SMEs suggested a similar inter-organizational factor, supplier trust (Sila, 2013).…”
Section: Identification Of Barriers and Facilitators Of The Degree Of Digital Usementioning
confidence: 99%